Performance evaluation of a near-surface earth-to-air heat exchanger with short-grass ground cover: an experimental study. (1st December 2019) - Pakari, Ali; Ghani, Saud
Highlights: Near-surface burial of the heat exchanger make installation and maintenance simple. The evapotranspiration from the grass cover lowers near-surface soil temperature. For an airflow rate of 607 m 3 /h, temperature drops as high as 6.5 °C were obtained. Relative to a conventional air conditioner about 76.5% energy savings are estimated. The near-surface earth-to-air heat exchanger will pay for itself in about 8.6 years. Abstract: Given the negative environmental impact and high energy consumption of conventional air conditioning systems, the use of passive cooling systems has become particularly important. An earth-to-air heat exchanger, which utilizes the earth as a heat sink, is an efficient passive cooling system. Conventional earth-to-air heat exchangers are buried in the soil at a great depth, to ensure the soil temperature is relatively lower than the ambient air temperature during the hot season. Therefore, due to the great burial depth, their installation and maintenance are usually problematic. An alternative is a near-surface earth-to-air heat exchanger with short-grass ground cover. The grass cover reduces the near-surface soil temperature, eliminating the need to bury the earth-to-air heat exchanger at a great depth. In this study, the performance of a near-surface earth-to-air heat exchanger with short-grass ground cover was assessed experimentally. For an airflow rate of 607 m 3 /h, equivalent to 9.24 m/s, the inlet air temperature was reduced from 40.6 °C to about 34.1 °C, corresponding to a coefficient of performance of 13.4. The soil temperature 0.5 m away from the earth-to-air heat exchanger was not affected by its operation. On a typical summer day, compared to conventional air conditioning systems, about 76.5% less energy would be consumed by the earth-to-air heat exchanger to provide the same amount of cooling. Therefore, using this earth-to-air heat exchanger as a precooling system in combination with conventional air conditioning systems can both protect the environment and save energy.